The relationship between political ideology and punishment: what do jury panel members say? - Clark, John W. (Applied psychology in criminal justice, 2012)
This study examines the effect of the self-identified political ideology of jurors and the tendency of those jurors to assess punishment. Significant research has been conductedthat suggests an individual's political ideology is a strong predictor of future behavior. Jury research is ripe with studies attempting to understand juror and jury decision making; however, no study we have found examines summoned jurors' self-identified political ideology and its relationship to punishment. Jurors from a large southwestern city were recruited to participate in this study. In all, 278 participants read a vignette containing a verbal and physical assault and responded to basic demographic questions as well as an attitudinal and ideological measure. We found that political ideology does not affect perceptions of guilt or length of sentence, but conservatives were more likely, controlling for other variables, to favor harsher fines on a perpetrator.